The CD133+ Stem/Progenitor-Like Cell Subset Is Increased in Human Milk and Peripheral Blood of HIV-Positive Women - Valverde-Villegas, Jacqueline María; Naranjo-Gomez, Mar; Durand, Mélusine; Rutagwera, David; Bedin, Anne-Sophie; Kankasa, Chipepo; Debiesse, Ségolène; Nagot, Nicolas; Tuaillon, Edouard; Van de Perre, Philippe; Molès, Jean-Pierre (Frontiers in Cellular and Infection Microbiology, 2020)
Human milk is a significant source of different CD133+ and/or CD34+ stem/progenitor-like cell subsets in healthy women but their cell distribution and percentages in this compartment of HIV-positive women have not been explored. To date, a decrease of CD34+ hematopoietic stem and progenitor cell frequencies in peripheral blood and bone marrow of HIV-positive patients has been reported. Herein, human milk and peripheral blood samples were collected between day 2–15 post-partum from HIV-positive and HIV-negative women, and cells were stained with stem cell markers and analyzed by flow cytometry. We report that the median percentage of CD45+/highCD34−CD133+ cell subset from milk and blood was significantly higher in HIV-positive than in HIV-negative women. The percentage of CD45dimCD34−CD133+ cell subset from blood was significantly higher in HIV-positive than HIV-negative women. Moreover, percentages of CD45dimCD34+, CD45dimCD34+CD133−, and CD45+highCD34+CD133− cell subsets from blood were significantly lower in HIV-positive than HIV-negative women. The CD133+ stem/progenitor-like cell subsets are increased in early human milk and blood of HIV-positive women and are differentially distributed to CD34+ cell subset frequencies which are decreased in blood.